The Mediating Role of Organizational Commitment in the Causal Relationship between Islamic Work Ethics and Psychological Empowerment with Job Performance of Employees of the Ministry of Sports and Youth - Kotobi, Fereshteh (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective:  The purpose of this study was to investigate the mediating role of organizational commitment in the causal relationship between Islamic work ethics and psychological empowerment with job performance of employees of the Ministry of Sports and Youth.Methodology: The research method is descriptive-correlational and applied in terms of purpose. The statistical population of this study was the staff of the Deputy for Management Development and Support Resources of the Ministry of Sports and Youth (290 people). According to Cochran's formula, the number of samples was 132. Data collection tools of this study were Ali and Al-Kazemi (1988) Islamic Work Ethics Questionnaire with 18 items, Spiritual and Mishra (1995) Psychological Empowerment Questionnaire with 15 items, Allen and Meyer (1990) Organizational Commitment Questionnaire with 24 items and Patterson Job Performance (1970) with 15 items. Structural equation modeling under Smart PLS3 software was used to investigate the research model and validate the hypotheses.Findings: The results show that the variable of Islamic work ethic has a positive and significant effect on organizational commitment. Also, the positive and significant effect of Islamic work ethic variable on job performance and psychological empowerment on organizational commitment was confirmed. The effect of psychological empowerment on job performance was also confirmed. Regarding mediation relations, it was found that organizational commitment mediates the effect of Islamic work ethic on job performance. Also, organizational commitment plays a mediating role in the relationship between psychological empowerment and job performance.Conclusion: Based on proposed model suggested that the managers of the Ministry of Sports and Youth increase the job performance of their employees by training and strengthening, Islamic work ethic and psychological empowerment.